The Analysis Effect of Brand Identity and Brand Image toward Brand Satisfaction and Brand Loyalty of Chocolate Product in Samarinda - suminto, Suminto; Martati, Indah; Kusrihandayani, Dyah; Estiyani, Erika (EDUTOURISM Journal Of Tourism Research, 2021)
This study aims to analyze the effect of brand identity and brand image on brand satisfaction and brand loyalty of silverqueen chocolate products in Samarinda City. A quantitative approach using path analysis processed with IBM SPSS 23 software and Structural Equation Modeling (SEM) with IBM AMOS 5 software. A total of 132 respondents who had consumed Silverqueen chocolate in Samarinda were the samples in this study. The measurement scale uses a Likert scale with a score of 1 - 5. In the beginning, validity and reliability tests are carried out on the research instrument, then estimation tests and structural model fit tests are conducted. The results showed that brand identity and brand image had a significant effect on brand satisfaction and had no significant effect on brand loyalty. Likewise, brand satisfaction has no significant effect on brand loyalty. The results of this study state that brand variables that affect brand satisfaction will not automatically encourage brand loyalty.